Estudio de la incidencia de reposo del textil con elastano en el tallaje de prendas de la empresa Piscis - Jerez Junta, Lissette Maritza (2024)
This project was developed within the cutting and sewing facilities of the Piscis company in the city of Ambato, which is dedicated to the manufacture of sports clothing and uniforms for different educational institutions. For the research, textiles with elastane that have greater rotation in the company were used, which allowed the respective experimentation to be carried out and each important aspect to be analyzed in detail within different rest times, thus contributing to knowledge on the subject. The project was developed at the facilities of Piscis, a company dedicated to the production of sports clothing and uniforms. The effect of resting textiles with elastane on the sizing of the garments was investigated. Elastane, essential in the textile industry due to its elasticity, influences the comfort and fit of garments. However, during rest, their behavior can alter the sizing, generating customer dissatisfaction. Measurements were made at different rest periods, revealing a significant influence on the final dimensions of the garments and on the customer's perception. To carry out the study, measurements of the dimensions of the samples were made at different rest times. The results highlight the importance of considering the rest time of the spandex textile in the manufacturing process, in order to ensure consistency in the dimensions of the garments and, ultimately, guarantee customer satisfaction and product quality. .